Study on the Interaction of Serum Albumin and Micromolecule Compounds - Rui Huang; Zhi-Ning Xia; Min Yi; Bo-Lin Liu (E-Journal of Chemistry)
Fluorescence spectrometry is a classical and conventional technique widely used in interaction investigation, which takes serum albumin as the fluorescence source while micro-molecule compound as the quencher. With analyzing the properties of serum albumin and its amino acids, deficiencies in the conventional fluorescence spectrometry became obvious: information expressed by the conventional technique was not sufficient to represent the entire interaction. In consideration of that, a new method was proposed to improve the conventional one. Intercompared the experimental results of those two methods, defects of the conventional fluorescence spectrometry were noticeable. In addition, molecular docking simulation and binding force investigation also manifested the same as above.